Kategorisasi Epistemologi Islam (Parepatetis, Illuminatis, dan Muta’aliyah) - Hidayat Hidayat (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
Suhrawardi was a philosopher who had a very important influence in the development of Islamic philosophy. The theory of illumination (isyraqi) which is the fruit of Suhrawardi's work has provided a new view in the development treasures of Islamic philosophy which has been dominated by the Paripatetism since before. The birth of the Illumination School (Israqi) is an alternative to the weaknesses that exist in previous philosophies, especially Aristotelian peripatetics. According to Suhrawardi, the peripatetic philosophy which until then was considered the most superior turned out to contain various shortcomings. After seeing how big the influence of the philosophy of illumination in the discourse on the development of Islamic philosophy is, then conducting a study of it in depth and comprehensively becomes a very important thing to do. Therefore in this study will be discussed about; How about Suhrawardi's theory of illumination knowledge? And how did it contribute to the development of Islamic philosophy?